Isolasi dan Seleksi Bakteri Antagonis Sebagai Alternatif Pengendalian Penyakit Layu Stroberi - SANJAYA, I GUSTI NGURAH PRABU WIRA; WIRYA, GUSTI NGURAH ALIT SUSANTA; PHABIOLA, TRISNA AGUNG; WINANTARA, I MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.8, No.2, April 2019, 2019)
Isolation and Selection of Antagonis Bacteria as an Alternative Control of Strawberry Wilt Diseases               Strawberry ( Fragaria sp .) is a plant that can produce fruit and a members of Rosaceae familia that entered Indonesia in the 1980s and began cultivativated in Candi Kuning Village, Bali at 1983. The farmer reported in 2017 at Candi Kuning Village, Bali, there are many strawberries plants are exposed to wilting disease caused by Fusarium oxysporum which can decreased strawberry production up to 80%. The purpose of this study is to find alternatives ways of chemical control that can cause environmental damage. Biological control, especially the use of antagonistic bacteria, has potential as a replacement because it is much more environmentally friendly and can create sustainable agriculture. The method used are isolation and selection, in vitro inhibitory test, and hypersensitive test on tobacco plants. Research activities included (1) sampling, (2) Fusarium oxysporum isolation from symptomatic strawberry plants, (3) isolation and selection of antagonistic bacterial candidates, (4) antagonistic candidate bacteria inhibitory test against Fusarium oxysporum by dual cultur method in vitro, and (5) hypersensitive test of antagonistic bacterial candidates on tobacco plant leaves. The result of this research is Fusarium oxysporum successfully isolated, obtained 24 candidates of antagonistic bacteria and only 4 candidates of antagonistic bacterial isolates capable of well inhibiting the development of Fusarium oxysporum with the average inhibitory percentage are more than 60 % which is the best inhibitory percentage of 90.17 % and in the hypersensitive test, the bacterial candidates tested were non-pathogenic to the plant.